PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA USAHA PERCETAKAN ALFA STUDIO DI MERLUNG KABUPATEN TANJUNG JABUNG BARAT - Victor Diwantara; Sissah Sissah; M.Redhoval Wahyu Saputra (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Globalization currently means that human needs and desires continue to develop and are not limited along with the times. Competition in the business world is increasingly difficult in the era of globalization. Economic development causes an increase in product variety. Consumers are satisfied with good service quality, product quality that shows its function and prices that reflect quality. Alfa Studio is able to ensure product quality and customer satisfaction by providing professional photographer direction and training by Alfa Studio to attract market attention. Alfa Studio implements a pricing policy that has an impact on consumer satisfaction. This research aims to determine and analyze the influence of product quality and price on consumer satisfaction.The method used in this research is a quantitative method, and the data analysis method used is the coefficient of determination test. The sample in this study was 68 samples.Based on the results of the t test on the product quality variable, the significance value is 0.00 > 0.05. then the Price variable with a significance value of 0.002 > 0.05. The significance value for the product quality (X1) and price (X2) variables simultaneously on consumer satisfaction (Y) is 0.00 > 0.05. From the hypothesis test it can be concluded, Ha1, Ha2, Ha3 are accepted, thus all hypotheses are accepted. It is recommended that the people of Merlung, West Tanjung Jabung Regency better understand the influence of product quality and price on consumer satisfaction at the Alfa Studio printing business in Merlung, West Tanjung Jabung Regency. Then in future research, it is hoped that other variables will be added to influence consumer satisfaction.